A Teaching Doctorate? The Doctor of Arts Degree, Then and Now - Glazer, Judith S.; American Association for Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This study examined the Doctor of Arts (DA) degree and its current status. The DA was established in the 1960s and was designed to foster college teaching and to prepare faculty to teach more effectively. The study's first phase included mail and telephone surveys of all institutions offering the DA degrees as well as those institutions that had discontinued it between 1976 and 1988, site visits to nine universities offering the DA, and interviews with current and former programs personnel involved in the programs. The second phase of the study consisted of a national survey of 350 DA degree recipients from 14 universities. Survey data were tabulated and content-analyzed in program choice, academic experience, outcomes of participation, and participant satisfaction. Results found that the DA had the impact of encouraging faculty to rethink the purposes of the doctorate and freeing students who aspired to teach undergraduates from the rigid requirements of the research doctorate. Responses from the survey of graduates revealed that a combination of factors influenced their decision to choose the DA: they are secure in their careers; their satisfaction is high; and two thirds would make similar choices today. An appendix contains the survey of graduates and information on American Association for Higher Education. (JB)
Availability: American Association for Higher Education, One Dupont Circle, Suite 360, Washington, DC 20036-1110 (
Sponsoring Agency: Teachers Insurance and Annuity Association, New York, NY. College Retirement Equities Fund.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Attitudes; Doctor of Arts Degrees; Doctoral Degrees; Graduate Students; Graduate Study; Higher Education; Outcomes of Education; Program Design; Program Development; Program Evaluation; Teacher Attitudes; Reports, Research